Based on molecular structures: Amyloid-β generation, clearance, toxicity and therapeutic strategies - Yang, Hai; Li, Jinping; Li, Xiaoxiong; Ma, Linqiu; Hou, Mingliang; Zhou, Huadong; Zhou, Rui (Frontiers in Molecular Neuroscience, 2022)
Amyloid-β (Aβ) has long been considered as one of the most important pathogenic factors in Alzheimer’s disease (AD), but the specific pathogenic mechanism of Aβ is still not completely understood. In recent years, the development of structural biology technology has led to new understandings about Aβ molecular structures, Aβ generation and clearance from the brain and peripheral tissues, and its pathological toxicity. The purpose of the review is to discuss Aβ metabolism and toxicity, and the therapeutic strategy of AD based on the latest progress in molecular structures of Aβ. The Aβ structure at the atomic level has been analyzed, which provides a new and refined perspective to comprehend the role of Aβ in AD and to formulate therapeutic strategies of AD.